2019
DOI: 10.1007/s12264-019-00401-9
|View full text |Cite
|
Sign up to set email alerts
|

Connections Between Insomnia and Cognitive Aging

Abstract: Insomnia is a common sleep disorder among older adults, and a risk factor for poor physical and mental health. However, the relationship between insomnia and cognitive health is not well understood. Here, we review observational studies that have investigated whether insomnia is associated with deficits in objective cognitive performance and an increased risk of dementia, magnetic resonance imaging studies that have assessed grey matter volumes and white matter microstructure, and interventional studies that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 51 publications
(63 reference statements)
2
36
0
1
Order By: Relevance
“…In addition, other neuroimaging meta-analyses have implicated structural and functional abnormalities in the hippocampus, amygdala, and insula in patients with sleep apnea 30 and have indicated convergent functional brain alterations in the inferior parietal cortex and superior parietal lobule, following acute sleep deprivation 31 . Moreover, white matter integrity underlying prefrontal areas has been associated with sleep duration and sleep quality [32][33][34] . Lastly, lower prefrontal gray matter volume has been associated with greater sleep fragmentation in older individuals 35 .…”
mentioning
confidence: 99%
“…In addition, other neuroimaging meta-analyses have implicated structural and functional abnormalities in the hippocampus, amygdala, and insula in patients with sleep apnea 30 and have indicated convergent functional brain alterations in the inferior parietal cortex and superior parietal lobule, following acute sleep deprivation 31 . Moreover, white matter integrity underlying prefrontal areas has been associated with sleep duration and sleep quality [32][33][34] . Lastly, lower prefrontal gray matter volume has been associated with greater sleep fragmentation in older individuals 35 .…”
mentioning
confidence: 99%
“…Based on these similarities between the pathophysiology of insomnia and mechanisms that cause AD including accumulation of Aβ, inflammation, and other components which are discussed in this review, insomnia disorder can be linked to AD risk [420][421][422] and this could be a novel target for treatments or prevention AD development and/or resolve the cognitive decline in patients with AD in the future [423].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged sleep disturbance predisposes a person to mental disorders, such as depression, anxiety, psychosis, and alcohol abuse [ 26 ]. A wide variety of physical diseases have been recognized to be associated with insomnia, e.g., cardiovascular diseases [ 27 ], dementia and cognitive decline [ 28 , 29 ], and obesity [ 30 ]. A large cohort study found a three-fold increased mortality risk in individuals with short sleep duration and persistent symptoms of insomnia [ 31 ].…”
Section: Perioperative Sleep Disturbancesmentioning
confidence: 99%